109=m+94

Simple and best practice solution for 109=m+94 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 109=m+94 equation:



109=m+94
We move all terms to the left:
109-(m+94)=0
We get rid of parentheses
-m-94+109=0
We add all the numbers together, and all the variables
-1m+15=0
We move all terms containing m to the left, all other terms to the right
-m=-15
m=-15/-1
m=+15

See similar equations:

| -4+-9c=41 | | 48*(3/4)=x | | 108=m+94 | | 92=2(j+20) | | 96=6(c+2) | | 5x+2=46 | | 2x+(-5)=(-1) | | 11x+79=40x+50 | | 7(h+33)=-98 | | 10+12x=15+1 | | 2(a-1)+1=3 | | 12x=10000 | | x-34=11/2 | | 2/8j+2=6 | | 4x+22=8x+22 | | –40=–8(x + 2) | | x+4.2=5.4 | | -15f-11=16-12f | | 7a+2a=27 | | 3(2y+4)=-3(-y+1) | | (6x+14)+(8x−12)=180 | | 3d+18=99 | | 3m+27=84 | | c-58=307 | | d. 145÷X=29 | | 3(w-4)=6(7-w) | | (3x+8)=(2x-2) | | 2.8=−0.9+x | | w/8+44=46 | | 1=k/4-5 | | y-(1-2)+(y-3)=-4 | | 3x+2=4) |

Equations solver categories